Edoxaban, Rivaroxaban, or Apixaban for Cancer-Associated Venous Thromboembolism in the Real World: Insights from the COMMAND VTE Registry-2 - Sueta, Daisuke; Yamashita, Yugo; Morimoto, Takeshi; Chatani, Ryuki; Nishimoto, Yuji; Kaneda, Kazuhisa; Ikeda, Nobutaka; Kobayashi, Yohei; Ikeda, Satoshi; Kim, Kitae; Inoko, Moriaki; Takase, Toru; Tsuji, Shuhei; Oi, Maki; Takada, Takuma; Otsui, Kazunori; Sakamoto, Jiro; Ogihara, Yoshito; Inoue, Takeshi; Usami, Shunsuke; Chen, Po-Min; Togi, Kiyonori; Koitabashi, Norimichi; Hiramori, Seiichi; Doi, Kosuke; Mabuchi, Hiroshi; Tsuyuki, Yoshiaki; Murata, Koichiro; Takabayashi, Kensuke; Nakai, Hisato; Shioyama, Wataru; Dohke, Tomohiro; Nishikawa, Ryusuke; Kimura, Takeshi; Tsujita, Kenichi; On behalf of the COMMAND VTE Registry-2 Investigators (Thrombosis and Haemostasis, 2024)
Background Real-world data on clinical characteristics and outcomes related to the use of different direct oral anticoagulants (DOACs) for cancer-associated venous thromboembolism (VTE) is lacking.Methods The COMMAND VTE Registry-2 is a multicenter registry enrolling 5,197 consecutive patients with acute symptomatic VTE from 31 centers in Japan from January 2015 to August 2020. Our study population comprised 1,197 patients with active cancer who were divided into the edoxaban (N = 643, 54%), rivaroxaban (N = 297, 25%), and apixaban (N = 257, 22%) groups.Results The cumulative 5-year incidence of recurrent VTE (9.3, 10.2, and 8.5%, respectively, p = 0.82) and all-cause death (67.5, 66.8, and 63.8%, respectively, p = 0.22) did not differ among the groups. Despite adjusting for confounders, the risks of recurrent VTE and all-cause death did not differ significantly among the groups. The cumulative 5-year incidence of major and clinically relevant bleeding was significantly lower in the rivaroxaban group than those in the other groups (22.6, 14.0, and 22.8%, p = 0.04; and 37.6, 26.8, and 38.3%, p = 0.01, respectively). After adjusting for confounders, in the rivaroxaban group, the risk for major bleeding was numerically lower (hazard ratio [HR]: 0.65, 95% confidence interval [CI]: 0.40–1.01) and that of clinically relevant all bleeding was significantly lower (HR: 0.67, 95% CI: 0.48–0.92) than those in the edoxaban group.Conclusion The risks of recurrent VTE and all-cause death did not differ significantly among the different DOACs ; however, the risk of bleeding events could differ, with a potentially lower risk of bleeding with rivaroxaban.
Keywords: venous thromboembolism; cancer-associated VTE; DOACs